2004
DOI: 10.1016/j.clinph.2003.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of motor cortex excitability after upper limb immobilization

Abstract: Objective: To examine the mechanisms of disuse-induced plasticity following long-term limb immobilization. Methods: We studied 9 subjects, who underwent left upper limb immobilization for unilateral wrist fractures. All subjects were examined immediately after splint removal. Cortical motor maps, resting motor threshold (RMT), motor evoked potential (MEP) latency and MEP recruitment curves were studied from abductor pollicis brevis (APB) and flexor carpi radialis (FCR) muscles with single pulse transcranial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 64 publications
11
67
1
2
Order By: Relevance
“…Although at the level of SCI lesion, a regenerative sprouting of interneurons may occur, above the lesion descending corticospinal axons extend new collaterals, and in the motor cortex new neurons are recruited along with the redistribution of projection neurons. The activation of functionally intact corticospinal neurons may depolarize a larger fraction of the 40 A recent study reported significantly increased active motor threshold in patients with incomplete cervical SCI. 18 This result was explained by the low density of motoneurons that innervate the hand muscles and seems to be in contrast with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although at the level of SCI lesion, a regenerative sprouting of interneurons may occur, above the lesion descending corticospinal axons extend new collaterals, and in the motor cortex new neurons are recruited along with the redistribution of projection neurons. The activation of functionally intact corticospinal neurons may depolarize a larger fraction of the 40 A recent study reported significantly increased active motor threshold in patients with incomplete cervical SCI. 18 This result was explained by the low density of motoneurons that innervate the hand muscles and seems to be in contrast with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…TMS of the motor cortex has been used to study plastic changes in cortical excitability associated with immobilization (Liepert et al, 1995;Zanette et al, 1997Zanette et al, , 2004Facchini et al, 2002;Huber et al, 2006). Although these studies yielded conflicting findings, a likely result was that even a short-term non-use is able to induce a decrease of cortical excitability in the motor area related to the restricted muscles (Facchini et al, 2002;Huber et al, 2006), probably because of the induction of local synaptic depression (Huber et al, 2006).…”
Section: Immobilization Effectmentioning
confidence: 99%
“…The injury might have altered corticospinal excitability and plasticity (Facchini et al 2002;Zanette et al 2004). …”
Section: Methodsmentioning
confidence: 99%